Cognitive subtypes in non-affected siblings of schizophrenia patients: characteristics and profile congruency with affected family members. Issue 2 (January 2014) - Quee, P. J.; Alizadeh, B. Z.; Aleman, A.; van den Heuvel, E. R.; GROUP Investigators
<x content-type="archive" xml:space="preserve">Abstract</x> Background Although cognitive subtypes have been suggested in schizophrenia patients, similar analyses have not been carried out in their non-affected siblings. Subtype classification may provide more insight into genetically driven variation in cognitive function. We investigated cognitive subtypes in siblings. Method Cluster analyses were performed in 654 non-affected siblings, on a cognitive battery that included tests of attention, intellectual function and episodic memory. Resulting subtypes in the siblings were analyzed for cognitive, demographic and clinical characteristics and compared with those of their probands. Results Three sibling subtypes of cognitive function were distinguished: 'normal', 'mixed' and 'impaired'. Normal profile siblings (n = 192) were unimpaired on cognitive tests, in contrast to their proband (n = 184). Mixed profile siblings (n = 228) and their probands (n = 222) had a more similar performance pattern. Impaired profile siblings had poorer functional outcomes (n = 234) and their profile was almost identical to that of their proband (n = 223). Probands with cognitively impaired siblings could be distinguished from other schizophrenia patients by their own cognitive performance. They also had poorer clinical characteristics, including achievement of symptomatic remission. Conclusions Unaffected siblings of patients with schizophrenia are heterogeneous with respect to cognitive function. The poorer the cognitive profile of the sibling, the higher the level of correspondence with the proband. The sibling's cognitive subtype was predictive for disease course in the proband. Distinguishing cognitive subtypes of unaffected siblings may be of relevance for genetic studies.